Curriculum Of Love: Efforts To Revitalise Humanism In Islamic Education - Eva Sunarya; Komarudin Sassi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study analyses the concept of a love-based curriculum as an effort to revive the humanistic side of students within the framework of Islamic education, as well as its potential implications for the learning management system in religious educational institutions in Indonesia. This study uses a systematic literature review methodology, analysing relevant literature published mainly since 2020. Data collection involved a comprehensive examination of official policy documents from the Indonesian Ministry of Religious Affairs, academic journals, and scientific publications through databases including Google Scholar, ERIC, JSTOR, and DOAJ. The analysis used thematic categorisation to identify key conceptual elements. This study identifies three fundamental dimensions of love-based curriculum: its philosophical foundation in the Islamic concept of rahmatan lil 'alamin, its pedagogical emphasis on emotional intelligence development, and its practical implementation challenges. This study contributes to educational theory by proposing a conceptual framework that bridges Islamic educational principles with contemporary humanistic pedagogy. These findings suggest practical applications for curriculum development in religious educational institutions facing the challenges of modernisation. This study presents the first comprehensive conceptual analysis of love-based curriculum initiatives in the context of Indonesian Islamic education, offering insights that transcend religious boundaries towards broader considerations of educational reform.